COMPOSITIONAL AND STRUCTURAL CONTROL OF FISSION-TRACK ANNEALING IN APATITE - Barbarand J.; Carter A.; Wood I.; Hurford T. (My University, 2003)
Geological cooling histories modelled from apatite fission-track (FT) data are dependent upon extrapolated, laboratory-based track annealing data. Annealing in apatite appears to be compositionally controlled. This study investigates how compositional variation influences apatite crystal structure (as reflected in the unit-cell parameters) and fission-track annealing, and then considers how best to monitor bulk composition in a practical way for routine fission-track analysis.New fission-track annealing data are presented for a series of 10-, 100- and 1000-h experiments on 13 apatite samples of different chemical composition. The bulk apatite composition of these samples was determined using uranium mapping, cathodoluminescence (CL), electron microprobe, inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma atomic emission spectrometry (ICP-AES) and spectrophotometry techniques, and their cell parameters characterised by X-ray powder diffractometry (XRD).Apatite structure reflects apatite bulk composition and unit-cell dimensions are changed by the complex interactions between anion substitutions (Cl, F, OH) and cation substitution (REE, Mn, Sr). While chlorine has a dominant control on apatite structure above 0.1 anion per formula unit (~0.35 wt.%), below this value other elements, in particular REE, exert a significant control. This study shows that the rate of fission-track annealing correlates with apatite structure, the annealing rate being slower for crystals with larger values for cell parameter a and smaller values for cell parameter c. In an earlier study, Carlson et al. [Am. Mineral. 84 (1999) 1213] found this correlation to be valid only for apatites of certain compositions.Ideally, the bulk composition and/or unit cell should be measured for each apatite grain analysed by the fission-track method to determine the appropriate track annealing parameters for use in thermal history prediction. Neither approach is a practical reality for routine analysis. The relative merits of determining chlorine content, the major influence on fission-track annealing, and using apatite solubility by measuring etch-pit sizes are discussed as practical alternatives for assessing the annealing response of individual apatite crystals.
Keywords: APATITE FISSION-TRACK THERMOCHRONOLOGY; FISSION-TRACK ANNEALING; APATITE COMPOSITION; UNIT-CELL PARAMETERS; THERMAL HISTORY PREDICTION